2020
DOI: 10.1192/bjp.2020.143
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain abnormalities in schizophrenia in adverse environments: examining the effect of poverty and violence in six Latin American cities

Abstract: Summary Background Social and environmental factors such as poverty or violence modulate the risk and course of schizophrenia. However, how they affect the brain in patients with psychosis remains unclear. Aims We studied how environmental factors are related to brain structure in patients with schizophrenia and controls in Latin America, where these factors are large and unequally distributed. Method This is a multicentre study of magnetic resonance imaging in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A study of the Philadelphia Neurodevelopmental Cohort (USA) (Gur et al, 2019) found that lower SES was related to both reduced performances in different cognitive domains and lower volume across brain regions, including white and gray matter, that was related to an accelerated neurodevelopment. In patients from Latin America (Crossley et al, 2021), we recently showed that income was related to total gray matter volume in unaffected individuals but not in psychosis patients. This potentially indicated that less brain vulnerability in patients (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study of the Philadelphia Neurodevelopmental Cohort (USA) (Gur et al, 2019) found that lower SES was related to both reduced performances in different cognitive domains and lower volume across brain regions, including white and gray matter, that was related to an accelerated neurodevelopment. In patients from Latin America (Crossley et al, 2021), we recently showed that income was related to total gray matter volume in unaffected individuals but not in psychosis patients. This potentially indicated that less brain vulnerability in patients (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…This potentially indicated that less brain vulnerability in patients (e.g. less gray matter loss) would be sufficient to become unwell in adverse environments, and that considering the upbringing of patients is critical to understanding schizophrenia's anatomy (Crossley et al, 2021). Although this may seem contradictory to the present report, we believe that these two Latin American findings indicate that environmental variables might be key to explaining disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate this point, a recent study included structural MRI images from 334 patients with schizophrenia and 262 controls and was able to examine the modulating effect of poverty and violence on the brain in the harsh Latin American environment. 86 Currently, projects are analyzing previously acquired genetic data to examine the validity of PRS for Latin American populations.…”
Section: Description Of Ongoing Projects and The Results So Farmentioning
confidence: 99%
“…MRI, neuropsychological assessments). To date, we have conducted studies on metabolic syndrome and healthy lifestyle 7 , neuroimaging 8 , treatment resistance 9 , social determinants of mental health 10 , epidemiology 11 , and public policies 6 , among other topics. This case report describes the potential benefits and associated challenges of conducting research in the context of a clinical practice in Latin America that works with vulnerable populations who have difficulties with decisional capacity.…”
Section: Case 1 a First Episode Of Psychosis Clinic In Latin Americamentioning
confidence: 99%